Al Murunah Regional Workshop Proceedings - Abeyrathna, Wasudha Prabodhani; Fragaszy, Stephen; Samarasekara, Vidhisha (International Water Management Institute, 2024)
The Al Murunah Regional Workshop, held from March 4–6, 2024, at the Geneva Hotel in Amman, Jordan, convened stakeholders and partners involved in advancing resilient nature-based water solutions (RNBWS). Organized by the International Water Management Institute (IWMI), in collaboration with the International Union for Conservation of Nature (IUCN) and country implementation partners (CIP) including the Society for the Protection of Nature in Lebanon (SPNL), Centre for Environment and Development for the Arab Region and Europe (CEDARE) in Egypt, and the Palestinian Hydrology Group (PHG) in the occupied Palestine territories , the workshop served as a pivotal moment in advancing collaborative efforts toward sustainable water management practices in the region.